Relationship Between Dietary Patterns and Cognitive Function in Older Adults in USA - Oliver, James (International Journal of Food Sciences, 2023)
Purpose: The aim of the study was to investigate relationship between dietary patterns and cognitive function in older adults. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Dietary patterns significantly influence cognitive function in older adults. Adherence to the Mediterranean diet is associated with reduced cognitive decline risk. Nutritional components like walnuts can enhance memory and executive function. The ketogenic diet shows promise for improving cognitive function, particularly in mild cognitive impairment cases. Cultural diets impact cognitive outcomes, with traditional diets often linked to better cognitive performance. These findings highlight the crucial role of diet in preserving cognitive health in older populations and underscore the need for tailored dietary recommendations across diverse contexts. Unique Contribution to Theory, Practice and Policy: Mediterranean diet theory, the micronutrient-related dietary pattern theory, the dietary pattern index theory may be used to anchor future studies on relationship between dietary patterns and cognitive function in older adults. Promote community-based interventions that provide older adults with access to affordable, nutritious foods and opportunities for social engagement. Policy makers should recognize the importance of a balanced diet for cognitive health and reflect this in public health recommendations.